AUTHENTICATION DEVICE, AUTHENTICATION SYSTEM, AUTHENTICATION METHOD, AND PROGRAM - MAENO KAZUKI; YOSHIO HIROAKI; OGURA YASUNOBU; TAMURA HAJIME (2020)
To accurately identify a person even if the appearance of the face of the person changes from an image registered with a passport or the like regarding an object whose appearance changes over time.SOLUTION: An authentication device (server device) of an authentication system includes: an acquisition unit (communication unit) that acquires first image data indicating the face of an animal to be authenticated, age information for identifying an age of the animal when the first image data was generated, second image data indicating the face of the animal generated later than the first image data, and aged information for identifying the number of years from the time when the first image data was generated to the time when the second image data was generated; and a control unit that collates the first image data with the second image data. The control unit calculates the degree of similarity of the face of the animal based on the first image data and the second image data, corrects the degree of similarity based on the age information and the aged information, and determines the sameness of the animal of the first image data and the animal of the second image data based on the corrected degree of similarity.SELECTED DRAWING: Figure 2 【課題】経年に伴って見かけが変化する対象について、本人の顔の見かけが、パスポート等に登録されている画像から変化していても、精度良く、本人確認する。【解決手段】認証システムの認証装置（サーバ装置）は、認証対象である動物の顔を示す第１の画像データと、第１の画像データが生成されたときの動物の年齢を特定する年齢情報と、第１の画像データよりも後に生成された動物の顔を示す第２の画像データと、第１の画像データが生成されたときから第２の画像データが生成されたときまでの経年数を特定する経年情報とを取得する取得部（通信部）と、第１の画像データと第２の画像データとを照合する制御部と、を備える。制御部は、第１の画像データと第２の画像データとに基づいて、動物の顔の類似度を算出し、年齢情報と経年情報とに基づいて類似度を補正し、補正した類似度に基づいて、第１の画像データの動物と第２の画像データの動物の同一性を判断する。【選択図】図２